2009
DOI: 10.1107/s090904950904240x
|View full text |Cite
|
Sign up to set email alerts
|

Diffractive–refractive optics: X-ray splitter

Abstract: The possibility of splitting a thin (e.g. undulator) X-ray beam based on diffraction-refraction effects is discussed. The beam is diffracted from a crystal whose diffracting surface has the shape of a roof with the ridge lying in the plane of diffraction. The crystal is cut asymmetrically. One half of the beam impinges on the left-hand part of the roof and the other half impinges on the right-hand side of the roof. Owing to refraction the left part of the beam is deviated to the left whereas the right part is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A new monochromator acting as an X-ray splitter was proposed by Hrdý (2010) and it was shown that this device also separates the first harmonic from the higher harmonics. However, its roof-shape is somewhat complicated and more demanding for fabrication.…”
Section: Monochromator Designmentioning
confidence: 99%
See 2 more Smart Citations
“…A new monochromator acting as an X-ray splitter was proposed by Hrdý (2010) and it was shown that this device also separates the first harmonic from the higher harmonics. However, its roof-shape is somewhat complicated and more demanding for fabrication.…”
Section: Monochromator Designmentioning
confidence: 99%
“…the harmonics can be easily separated by slits. As follows from Hrdý (2010), the deviation may be substantially enhanced if asymmetric crystals are used. However, the asymmetry may delimit the usable wavelength range of the monochromator.…”
Section: Monochromator Designmentioning
confidence: 99%
See 1 more Smart Citation